Synthesis, Pyrolytic, and Antibacterial Study of 3-[(E)-(2-phenylhydrazinylidene)methyl]pyridine(PHMP) and Its Transition Metal Complexes. Issue 11 (1st November 2016) - Rehman, Saeed-ur-; Faiz, Alia; Nawaz, Robila; Ali, Nauman
Abstract : Phenyl hydrazine and pyridine-3-carbaldehyde were coupled to form a new Schiff base 3-[( E )-(2-phenylhydrazinylidene)methyl]pyridine(PHMP), followed by the formation of its transition metal derivatives (i.e., Co(II), Cu(II), and Zn(II) complexes). All of them were characterized by physical and spectral methods such as 1 H-NMR, IR, elemental analysis, UV-Vis spectra, and conductance studies. Thermal study was carried out with TG/DTA method to understand the degradation pattern of the newly synthesized ligand and its complexes. Antibacterial study was carried out with both the gram-positive ( Bacillus subtilis, Staphylococcus aureus, Staphylococcus epidermis, Streptococcus pneumonia) and gram-negative bacteria ( Pseudomonas aeruginosa, Salmonella typhi, Escherichia coli). The complexes showed medium activity as compared to the standard imipenem.